On the analysis of bonded step lap joints. (October 2018) - Jones, Rhys; Peng, Daren; Michopoulos, John G.; Phan, Nam; Berto, Filippo
Highlights: It confirms that the ESDU multi-step lap joint code and the USAF lap joint code A4EI both give similar results. It confirms that the Glinka approximation holds for symmetric double lap joints. It reveals that the Glinka approximation also appears to hold for multi-step lap joints. It reveals that the results are invalid in the adherends. It suggests a simple method for allowing for combined load states. Abstract: This paper discusses the stress and strain states in adhesively bonded step lap joints from the perspective of the strain energy density solutions determined via the elastic and elastic-plastic solutions obtained using the computer code A4EI, which as outlined in the US Defence Departments Composite Materials Handbook CMH-17-3G, is the industry standard for designing adhesively bonded joints. Whereas it has previously been shown that the load carrying capacity of an adhesively bonded double lap joint could be estimated using the strain energy density associated with the elastic solution and the critical value of the adhesive strain energy density, the present paper reveals that this approach also yields a reasonable first approximation for the load carrying capacity bonded step lap joints.